Pembuatan Bahan Ajar Digital Pada Mata Pelajaran Ekonomi Bisnis - Dea Tiara Monalisa Butar-Butar; Lisa Paramita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Education is a field that must be prioritized because students have various potentials in themselves. The impact of Covid-19 has made significant changes to learning activities carried out in schools. The aim of this project is to find solutions to the problems faced by Harapan Utama Batam Vocational School by helping to create digital teaching materials to expedite the learning process with online methods.